Implementation of RESTful Web Service on Indonesian’s Integrated Breastfeeding Donor Information System - Badieah Badieah; Ahmad Mujib; Muna Yastuti Madrah; Andi Riansyah; Nur Muhammad Syaifuddin (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
The golden period is a term used to describe the importance of the first 1000 days of human life. Nutritional intake in children at this time becomes very important because malnutrition in this period will cause disturbances in child development. To prevent this risk, the intake of breast milk is necessary for babies at least in the first 6 months of life. However, there are many internal and external factors that can affect a baby not being able to receive it. One solution that commonly used to share breast milk amongst mothers. A mother can share breast milk directly through personal relations or through human milk bank agencies. The implication of the problem of sharing human milk in Muslim societies is the occurrence of kinship relationship between the child and his milk mother that change the status of mahram and the prohibition of marriage between breast milk children and biological children of the donor because the two children's status changed to breast milk siblings. Referring to these conditions, we designed an integrated information system prototype by integrating breast milk donor data obtained from human milk banks throughout Indonesia. Interoperability problems during data integration process are overcome by implementing a RESTful API as a web service. The output of this information system is the issuance of milk-kinship certificates given to donors and recipients as evidence of donors as well as become a token that there is a mahram bond between donors and recipients. A milk-kinship certificate can prevent marriage between milk-kinship siblings, especially in Muslim communities.